Challenging the Hegemony of the Grand Paradigm of Social Movement Studies: A Review of Paradigmatic Weaknesses - Joni Rusmanto; Ester Sonya Ulfarita; Muhammad Farid (Journal Ilmu Sosial, Politik dan Pemerintahan, 2023)
The study of social movements today is dominated by three grand paradigms (grand theory) in the 1980s, and even in Indonesia since the 70s. The three major paradigms of study are the "structural tension paradigm", the "resource mobilization paradigm", and the "identity-oriented paradigm", all of which have become the main sources of reference in various studies that have been developed. Through the literature review method, the critical analysis in this article aims to map, classify and categorize the grand theory and its influence on various social movement studies in Indonesia. The findings of this article show that the "structural tension" paradigm fails to consider how individuals experience dispossession as embedded in broader social structures. The "resource mobilization" paradigm places too much emphasis on collective action, which tends to be squeezed into market theory and consumerism. Placing the target achieved is only a political target, oriented towards the "economic man" (socios economiculus), which merely calculates a deterministic hedonistic calculus. While the "identity-oriented" paradigm fails when positioning the identity of new collective actors is recognized, then by themselves their expressive actions can be transformed into instrumental actions whose names can be seen clearly as a case of institutionalizing collective mobility. In conclusion, in many cases today's theorists have synthesized the insights of earlier older schools while adding dimensions that they overlooked. The overall trend, which one would like to focus on, is the clustering of large structures in favor of a concern with the micro-foundations of social and political action.